Emergency Preparedness Simulation Cases for Medical Students: Crush and Organophosphate Exposure - Nicholas Edward Kman; Daniel Bachmann; Austin Taylor Folley; Jeffery Adams; Marek Greer (Association of American Medical Colleges, 2013)
Abstract At many institutions, graduating medical students obtain minimal training related to managing and handling disaster scenarios, including but not limited to crush injuries and hazmat exposure. Regardless of specialty and degree of training, young physicians will be expected to help and treat patients should a catastrophe occur. The purpose of these simulation cases is to provide realistic scenarios pertaining to crush injury and hazardous material exposure for medical students. The two cases require students to make critical medical decisions in the setting of trauma or toxic contamination, as well as to learn the basics of exposure prophylaxis and decontamination. By using a mannequin and corresponding didactics from university faculty or local experts, the students are able to work as a team and simulate various disaster scenarios without the fear of making mistakes or harming real patients. Following each scenario, a 15-minute debriefing focusing on specific medical decisions and answering questions encountered during the case takes place. These scenarios were taught at the Ohio State University College of Medicine on March 26, 2012. We had 15 student participants and three clinical instructors. Students universally found the experience beneficial.